Konsep Dan Penerapan Sistem Informasi Manajemen - Safira Armah; Rayyan Firdaus (Jurnal Inovasi Manajemen, Kewirausahaan, Bisnis dan Digital, 2024)
The purpose of writing this article is to find out the concepts, benefits, applications and challenges experienced in Information Management Systems. Management Information System (MIS) is a very important and strategic system in the modern digital era. This system functions as the main means of collecting, processing and presenting relevant and accurate information to management, so that it can assist in making better decisions. In this article, researchers use the literature study research method to analyze data by describing data that has been collected from various sources such as books, journals, articles, research reports, and other sources that are relevant to the topic being studied. Through a literature study, this research explores the definition and main benefits of MIS, which is a combination of human resources, information technology, and procedures to produce quality information for decision making. Effective implementation of MIS can provide a competitive advantage for organizations in increasing productivity, efficiency and competitiveness. However, SIM implementation also faces various challenges, such as system integration, data security, data quality, user resistance, investment costs, rapid technological changes, and organizational complexity. This research contributes to providing a comprehensive understanding ofManagement Information Systems, as well as highlighting the importance of utilizing information as a strategic asset for organizations in achieving their business goals